Isolation and Characterization of Three Camel (Camelus dromedarius) Milk Casein fractions - E. S., Shuiep; S., Jäger; I. A. , Yousif; G., Erhardt (Journal of Veterinary Medicine and Animal Production, 2021)
This study was designed to isolate and characterize camel (C. dromedarius) milk caseins (CN) using Ion Exchange Chromatography (IEC), Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE) and Isoelectric Focusing (IEF) techniques. Whole camel casein was precipitated by means of acidification (pH 4.3), freeze-dried and then fractionated using IEC. Dissolved casein revealed three (I, II and III) well resolved peaks. Elutes representing different peaks were loaded together with whole camel milk on the same IEF gel to identify bands corresponding to each fraction based on their isoelectric points (pI). Elutes under peak I and II revealed a single band each corresponding to κ-CN and β-CN, respectively, while elute under peak III showed two bands corresponding to αs1-CN and β-CN. Band corresponding to αs1-CN fraction was focused on the most acidic side of the IEF gel followed by β-CN on the middle, while κ-CN was the less acidic fraction. Furthermore, casein fractions were subjected to SDS-PAGE, and their molecular masses were estimated at 36.325, 31.732 and 25.044 kDa, respectively. However αs2-CN was not detected and κ-CN was only observed in IEC product (due to low concentration in milk), β-CN fraction revealed the most intensive band on SDS-PAGE and IEF gel indicating its relatively higher content in camel milk.